Gate Alignment of Liquid Water Molecules in Electric Double Layer - Li, Xiaoqun; Lin, Xin; Li, Ying; Liu, Wei-Tao (Frontiers in Chemistry, 2021)
The behavior of liquid water molecules near an electrified interface is important to many disciplines of science and engineering. In this study, we applied an external gate potential to the silica/water interface via an electrolyte-insulator-semiconductor (EIS) junction to control the surface charging state. Without varying the ionic composition in water, the electrical gating allowed an efficient tuning of the interfacial charge density and field. Using the sum-frequency vibrational spectroscopy, we found a drastic enhancement of interfacial OH vibrational signals at high potential in weakly acidic water, which exceeded that from conventional bulk-silica/water interfaces even in strong basic solutions. Analysis of the spectra indicated that it was due to the alignment of liquid water molecules through the electric double layer, where the screening was weak because of the low ion density. Such a combination of strong field and weak screening demonstrates the unique tuning capability of the EIS scheme, and would allow us to investigate a wealth of phenomena at charged oxide/water interfaces.